2009
DOI: 10.1038/sj.bjc.6605449
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotype and molecular characterisation of adenocarcinoma of the small intestine

Abstract: BACKGROUND: Despite having a dramatically larger surface area than the large intestine, the small intestine is an infrequent site for the development of adenocarcinoma. To better understand the molecular abnormalities in small bowel adenocarcinoma (SBA), we characterised a number of candidate oncogenic pathways and the immunophenotype of this rare cancer. METHODS: Tissue microarrays were constructed from tumour samples from 54 patients with all stages of the disease. Immunohistochemistry and microsatellite ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
114
4
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(131 citation statements)
references
References 36 publications
10
114
4
3
Order By: Relevance
“…Only a few previously reported studies have undertaken CDX2 and/or mucin protein expression analysis on small intestinal adenocarcinomas. 11,21,34,35 However, due to the small number of patients who were evaluated in these earlier reports, insufficient data were available to determine the prognostic significance of the 16,17,19 However, no significant survival differences were observed in our current small intestinal adenocarcinoma cohort in terms of MUC1 protein expression, which is different from the findings in gastric cancer. Lee et al 11 have previously reported that duodenal cancers more frequently demonstrate MUC1 protein expression (10 of 14 cases; 71%) than jejunal and ileal cancers (2 of 9 cases; 22%), but they did not report any differences in terms of MUC5AC or MUC6 expression.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Only a few previously reported studies have undertaken CDX2 and/or mucin protein expression analysis on small intestinal adenocarcinomas. 11,21,34,35 However, due to the small number of patients who were evaluated in these earlier reports, insufficient data were available to determine the prognostic significance of the 16,17,19 However, no significant survival differences were observed in our current small intestinal adenocarcinoma cohort in terms of MUC1 protein expression, which is different from the findings in gastric cancer. Lee et al 11 have previously reported that duodenal cancers more frequently demonstrate MUC1 protein expression (10 of 14 cases; 71%) than jejunal and ileal cancers (2 of 9 cases; 22%), but they did not report any differences in terms of MUC5AC or MUC6 expression.…”
Section: Discussioncontrasting
confidence: 57%
“…Although a few studies have reported the expression patterns of CDX2 and mucin proteins in small intestinal adenocarcinomas and ampullary carcinomas, most of these analyses were performed on a small number of small intestinal adenocarcinoma patients. 11,13,21,[33][34][35][36][37][38] Moreover, to the best of our knowledge, no previous studies have investigated the prognostic significance of CDX2 and mucin expression in small intestinal adenocarcinomas.…”
mentioning
confidence: 99%
“…In an immunophenotypic analysis of SBA, the dominant pattern was CK20 positivity and CK7 negativity, which is seen in 75%-94% of colorectal cancer cases. Caudal-type homeobox transcription factor 2, which is highly expressed in colorectal cancer, was also expressed in most cases of SBA, especially in well-differentiated tumors [28]. In the genome-wide DNA copy number analysis, it was shown that the profiles of SBA overlapped more with colorectal adenocarcinoma than with gastric adenocarcinoma [29].…”
Section: Discussionmentioning
confidence: 95%
“…25,26 The main challenge for the near future is to identify molecular markers involved in small bowel carcinogenesis that predict chemosensitivity, and thus to improve survival. 5 Overman et al 27 observed that a high proportion of small intestinal adenocarcinomas express both EGFR and vascular endothelial growth factor (VEGF), suggesting that these patients may benefit from therapeutic strategies targeting EGFR and VEGF. Targeted therapies such as monoclonal antibodies against VEGF or EGFR combined with chemotherapy have already exhibited significant efficacy in metastatic colorectal cancers.…”
Section: Discussionmentioning
confidence: 99%